Study on the Relationship of Knitted Female Underwear Pressure Comfort and Loose Quantity (Journal of Fiber Bioengineering and Informatics, 2016)
The underwear fit and pressure comfort is a crucial importance. This paper firstly used the Untouched3D Body Scanner to scan the 110 young female body, and extracts a total of 17 human body sizes relatedto underwear structure, in all the directions including the horizontal directionvertical direction and otherdirection. Through analyzing the data, this paper focused on that among the horizontal dimensions:waist circumference, abdomen circumference, hip circumference, and the thigh root circumference;Vertical dimension: height, waist high; and other size: lower trunk length is the biggest difference,and the key part that affects the underwear specification. To analyze these measurement results andcontrast with the national female underwear shape series standard found that the most common isthe intermediate of A shape, at present, so regard the female intermediates as main object of study.Assess this knitting fabric is suitable for the middle of elastic underwear, through the test of fabric gramweight, warp ⁄ weft, thickness and elasticity. Moreover, this paper made the zero relaxation prototypewith inelastic fabric by utilized vertical cutting and pattern, combined with young women wearingpreferences, chose the female low-rise boxer briefs style as the main style of study. On this basis increaseto -4 cm relaxation in turn in the Abdominal girth, hip girth and thigh girth, fork reduce 0.5 cmin turn. According to this regular to make five different relaxation knitted female underwear, andinvites eight eligible subjects to put on the underwear to complete a series of dynamic testing, at thesame time, gives the subjective evaluation timely for each related panties pressure comfort under thecondition of different actions. Finally, With local comfortable stress evaluation method to evaluate thepressure when subjective human movement, the biggest impact of the site in turn, is abdominal, backhip, thigh, the bottom fork, based on analyzing the data, found that when abdomen circumference andhip circumference of the loose quantity is -17 cm, thigh circumference is -12 cm, and fork is 13 cm,people who wear this kind of knitted underwear can have the most comfortable feeling.